Infantaria de Mato Grosso : soldados, oficiais e Justiça Militar (1864-1914) - Farias, Aluísio Gonçalves de (2015)
This search has as object of study the Military Organizations in Mato Grosso, focusing on the Infantry, from 1864 to 1914. His interest in research on the Infantry is justified by lack of historical studies of this Infantary, plus the interest to observe the discipline and professional control to the military soldiers and officers from the Brazilian Imperial State was subject. The time frame covers the period from 1864 to 1914. The year 1864 refers to the beginning of the War with Paraguay, currently characterized by the creation and deployment of military bodies across the Paraguay invasions at the Brazilian Empire. The year of 1914 show the beginning professionalization and modernization of the Armed Forces, started in the military military government of Floriano Peixoto (1981-1894), and the formation of a "spirit of corps" which allowed cohesion and formation of a spirit of the role political military in the First Republic. Also denotes the beginning of the First World War (1914-1918). The study uses the approach of social history and its interface with the "New Military History" to understand the route of the continuities and ruptures of this Infantary. We evidence the approaches of Edward Palmer Thompson, Celso Castro, Fabio Faria Mendes and Peter Beattie. Among the many topics discussed, we focus on the study on the officers of Infantry who acted in Mato Grosso, during and after the War with Paraguay and in the early years of the Republic. We observed that a military career could be, for high-ranking officers, a kind of "stepping stone" to climb positions in the executive branch of a Province and / or State. The life trajectory of the military officers, helps us to reflect on the military presence in Mato Grosso in the second half of the nineteenth and early twentieth centuries, and its interface with society. Another aspect also studied in this search refers to the operation and organization of the Military Justice, regional and national level, pointing their formalities, components and the legal ritual for the trial of the defendant.